Comparative effects of single vs. double weekly plyometric training sessions on jump, sprint and change of directions abilities of elite youth football players - Bianchi, M.; Coratella, G.; Dello Lacono, A.; Beato, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Plyometrics are widely implemented as training methodology for enhancing functional sports performance. Although several studies have analyzed the plyometrics effects due to training plans with a frequency of 2-3 times a week, few of them provided evidence supporting an equal efficiency of similar training programs implementing lower training frequency such as one training session a week. METHODS: Twenty-one players (elite academy, Switzerland) were included in the current study (mean±SD; age 17±0.8 years, weight 70.1±6.4 kg, height 177.4±6.2 cm). This study used a randomised pre-post parallel group trial design. The participants were assigned to either a low-volume plyometric training group (LPG=10 participants) or a high-volume plyometric training group (HPG=11 participants). A long jump test, a single-leg triple hop test, sprint (10, 30 and 40 m) and 505 change of directions test were performed. RESULTS: Exercise-induced meaningful changes in performance for both LPG and HPG occurred after the training. LPG and HPG reported improvements in long jump (ES=1.0 and 0.77), triple hop right (ES=0.32 and 0.28), triple hop left (ES=0.46 and 0.32), 10 m sprint (ES=0.62 and 1.0). CONCLUSIONS: Both LPG and HPG are effective training modalities inducing benefits in jump and sprint tests for elite young football players. Fitness coaches and sports scientists could integrate their training plans with the protocols described in this study.